Real-time ultrasound guidance improves neonatal umbilical venous catheter placement efficiency and reduces liver complications - Tomaszkiewicz, Anna; Kruczek, Piotr; Szymański, Piotr; Walczak, Krystian; Teplicki, Piotr; Sobczak, Alina; Mazela, Jan (Frontiers in Pediatrics, 2025)
IntroductionUmbilical venous catheters (UVCs) are essential in neonatal intensive care, yet blind insertion techniques remain common and increase the risk of malposition and liver injury. This study evaluated whether real-time ultrasound guidance improves UVC placement efficiency and safety.MethodsWe retrospectively analysed 305 neonates who underwent ultrasound-guided UVC placement between July 2023 and January 2025 in a tertiary neonatal unit. The primary outcome was successful tip placement in the subdiaphragmatic vestibule; the secondary outcome was acute catheter-related liver injury.ResultsCorrect catheter placement was achieved in 86.56% of cases, with a gradual improvement from 83.81% to 89.12% over time. Only one hepatic haematoma was observed, and no other acute complications occurred.DiscussionReal-time ultrasound guidance significantly enhances the accuracy and safety of UVC insertion in neonates, minimising hepatic injury risk. Further research should assess its role in prolonged catheter monitoring.